Interaction of cationic surfactants with DNA: a single-molecule study - HEGNER, MARTIN (My University, 2008)
The interaction of cationic surfactants with single dsDNA molecules has been studied using forcemeasuring optical tweezers. For hydrophobic chains of length 12 and greater, pulling experiments show characteristic features (e.g. hysteresis between the pulling and relaxation curves, forceplateau along the force curves), typical of a condensed phase (compaction of a long DNA into a micron-sized particle). Depending on the length of the hydrophobic chain of the surfactant, we observe different mechanical behaviours of the complex (DNA-surfactants), which provide evidence for different binding modes. Taken together, our measurements suggest that short-chain surfactants, which do not induce any condensation, could lie down on the DNA surface and directly interact with the DNA grooves through hydrophobic? hydrophobic interactions. In contrast, longchain surfactants could have their aliphatic tails pointing away from the DNA surface, which could promote inter-molecular interactions between hydrophobic chains and subsequently favour DNA condensation.
PUBLISHED
Keywords: Physics